Exploring Student's Motivation in the Implementation of Multimodal Pedagogy Flipped Classroom: A Case Study - Sherly Pebriani Permana; Leni Irianti; Dedeh Rohayati (Universitas Galuh, 2026)
English speaking skills are often a challenge for university students due to anxiety, lack of confidence, and limited opportunities to practice in meaningful contexts. In higher education, especially in public speaking classes, there is still limited research on how innovative pedagogies such as flipped classrooms combined with multimodal strategies can enhance students' motivation and speaking performance. This study aimed at exploring students’ motivation in the implementation of multimodal pedagogy within a flipped classroom setting in a public speaking course. This research employed a qualitative case study design. The data were collected through classroom observations and semi-structured interviews with undergraduate students at a private university in Indonesia. The results indicate that intrinsic motivation was fostered through activities that allowed autonomy, creativity, and enjoyment, such as videos, group discussions, and multimedia presentations. Meanwhile, extrinsic motivation was driven by teacher feedback, peer recognition, and structured assessments, which promoted more active participation and speaking confidence. The integration of multimodal pedagogy in the flipped classroom supported diverse learning preferences and created a more student-centered environment. These findings suggest that thoughtfully integrating flipped learning and multimodal tools not only improves students’ public speaking competence but also enhances their overall motivation in language learning contexts. For further researcher suggested to broaden the research participant.